Spent nuclear fuel dry storage: status and current issues - Yatsenko, M.V.; Korolyov, A.V. (Вопросы атомной науки и техники, 2019)
Among all the options of spent nuclear storage, dry storage seems to be the most expedient method for the nearest future all over the world. Despite the economic attractiveness and the presence of a positive operating experience, there are still open questions. In this article author investigates the status of dry storage, gives a review of world experience and current issues that need to be solved to ensure safe long-term storage of spent nuclear fuel. Серед усіх варіантів зберігання відпрацьованого ядерного палива сухе зберігання представляється найбільш доцільним методом у найближчому майбутньому в усьому світі. Незважаючи на економічну привабливість і наявність позитивного досвіду роботи, залишаються відкриті питання. У цій статті автор досліджує стан сухого зберігання, дає огляд світового досвіду і поточних проблем, які необхідно вирішити, щоб забезпечити безпечне довгострокове зберігання відпрацьованого ядерного палива. Среди всех вариантов хранения отработавшего ядерного топлива сухое хранение представляется наиболее целесообразным методом в ближайшем будущем во всем мире. Несмотря на экономическую привлекательность и наличие положительного опыта работы, остаются открытые вопросы. В этой статье автор исследует состояние сухого хранения, дает обзор мирового опыта и текущих проблем, которые необходимо решить, чтобы обеспечить безопасное долгосрочное хранение отработанного ядерного топлива.